Perkembangan Teknologi Rapid Prototyping: Study Literatur - Rinanto, Andhy; Sutopo, Wahyudi (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2017)
Rapid prototyping technology continues to grow and widely used in the field of human life. The ability to form various objects makes RP technology can go anywhere easily. This literature study aims to determine rapid prototyping technology developments from the beginning to the present and to see future developments. Literature is selected from journals discussing manufacturing technology, its origins, of methods used, of integration with other fields and of the application of RP technology. Scopus used as other data source to know the development of RP research from year to year. Through the analytical facilities available at Scopus, it can be used to know the areas of human life that entered this technology. RP technology is still evolving and integrating with other fields. In the future, this technology will be easily accessible and accessible to everyone.